God's peculiar people : women's voices & folk tradition in a Pentecostal church - Lawless, Elaine J. (The University Press of Kentucky, 2005)
""Holy Rollers""--With this epithet most people dismiss members of the Pentecostal sect as wild religious fanatics. In this new study, folklorist Elaine Lawless draws on fieldwork among Pentecostal congregations in the limestone region of southern Indiana to offer a sympathetic view of the Pentecostals as a special group distinguished by their own folk traditions and religious expression. From her findings she describes the members' codes of dress and behavior, their attitudes toward themselves and others, their special use of words, and their distinctive religious practices. Focusing on the